Answer:
2x^2 + x - 6 = rectangular garden: <u><em>length = 2x – 3 feet; width = x + 2 feet</em></u>
Step-by-step explanation:
(2x - 3)(x + 2) = 2x^2 + x - 6 =
2x^2 + 4x - 3x - 6 = 2x^2 + x - 6 =
2x^2 + x - 6
You get the original equation from the two sides multiplied. :)
Hope this helps, have a good day.
25x=65
We divide 25 to cancel it out.
65/25=2.6
I would assume 3, because 2.6 is 3 when rounded up.
---
hope it helps
There was a time that a friend of mine got to a decision because the leader of the group said so (it was a group project). Although it was clear that he did not want to comply to the decision, he made it because it was what the leader said so.
Answer:
The system of equations has one solution. The two equations are intersecting lines.
Step-by-step explanation:
if you want to use the substitution method, you would have to plug in y for 12x+2 in the second equation.
2(12x+2)=x+4
next, you have to distribute
24x+4=x+4
subtract 24x from each side
4=-23x+4
subtract 4 from each side
0=23x
divide each side by 23
x=0
now, plug in 0 to one equation.
y=12(0)+2
y=2
the lines intersect at one point, (0,2)